Fatigue crack growth under rotating bending loading on aluminium alloy 7075-T6 and the effect of a steady torsion. (December 2015) - da Fonte, M.; Reis, L.; de Freitas, M.
Highlights: The effect of steady torsion on fatigue crack growth rate due to rotating bending rate is verified. The conditions for the retardation effect is presented and explained. Differences between fatigue crack growth rate under rotating bending and standard specimens. During one rotation of the crack in rotating bending, the crack experiences different levels of closure. Fractography in failure surfaces explain the closure effect leading to crack growth retardation. Abstract: Axles and shafts are of prime importance concerning safety in energy equipment, transportation industry and general machinery. Case studies relating failure of axles and shafts are widely reported in the literature. Design rules for axles and shafts are mainly based on endurance curves for the material used according to long time established standards and procedures. Safe life design, based on endurance curves is being complemented by damage tolerance, where crack growth is taken into account. Recently, the knowledge of fatigue crack growth under typical loading conditions of axles and shafts with rotating bending and steady torsion has been object of research in order to apply damage tolerance concepts, mainly for maintenance and failure analysis purposes. The effect of a steady torsion on fatigue crack growth under rotating bending is focused in this paper. While axles and shafts in the transportation industry are traditionally designed on steels, the need for weight reduction due to fuel economy and eco-design constraints, lightweight materials must be considered for these applications. In this study, fatigue crack growth on rotating bending axles and shafts with or without an applied steady torsion is presented. Fracture mechanics approaches are used to analyze the results based on stress intensity factors developed for bending and torsion in shafts. Results are compared for the same stress ratio and relevant differences on fatigue crack growth are commented based on crack closure concepts. Discussion of the effect of crack growth retardation due to steady torsion is also discussed. Fractographic observations are presented and helped to explain fatigue crack growth under this mixed mode loading when steady torsion is applied to rotating bending.